A new dimension in the value of corporate social responsibility: Demotivating undesirable job habits during crisis. (September 2022) - Lam, Cindia Ching Chi; Ma, Erdan; Im, Ut Lon (Billy); Hong, Wilson Cheong Hin; Zhao, Leyi
Abstract: Recent studies on the pandemic have focused on the DOs and DON'Ts of recovery remedies, but few have investigated the pandemic-spawned fundamental internal problems of the enterprises in order to diminish the impacts of the mega-crisis and relieve the need for recovery efforts. It is incontestable that employees are one of the major victims of the pandemic crisis; their negative emotions caused by the increasing career and financial instability have heightened the challenges of their enterprises that are striking for survival. This research has identified a breakthrough that extends the effect of CSR efforts from the traditional societal focus to internal employees, to whom CSR is found to mediate the undesirable escape habits and anti-crisis behaviours resulted from crises. This strengthens the understanding and value of CSR, while presents management with a novel mixed strategy to stabilize employee emotions and assemble their competence to get through a crisis.